PLATFORMIZING DELIVERY WORKERS' EXPERIENCES: BUILDING WORKER-OWNED PLATFORMS IN BRAZIL, SPAIN AND FRANCE - Grohmann, Rafael (AoIR Selected Papers of Internet Research, 2021)
The article aims to analyze the emergence of worker-owned platforms, specifically delivery workers’ experiences, as one of the laboratories of platform labor and the circulation of workers’ struggles Drawing on interviews with six cases in three different countries (Spain, France and Brazil), the research highlights the commonalities, specificities and challenges of platformizing delivery workers’ experiences in different countries. The analysis consider following dimensions: productive processes and work organization, technological challenges and building platforms, use of social media to communicate with and organize workers, and the future of worker-owned experiences. The initiatives had very different trajectories. In Spain, some cooperatives were born from union struggles. In France, we saw a strong relationship with CoopCycle, a federation of delivery co-ops that provides its own software based on the principles of digital commons. And in Brazil, small collectives and co-ops that still depend on social media platforms to execute their work are emerging. Despite different contexts, there are commonalities, such as the low number of workers, the central role of social media for communicating and organizing work, and the emergence of cooperation among cooperatives, which shows that scale does not need to be a standard in platform economies. The conclusions point out there is an ongoing and emerging process that can be the beginning of a broader process of reinventing local economic circuits of production and consumption that involves digital platforms for the common good.